MICROBIOLOGICAL ASSESSMENT OF INDOOR AIR QUALITY OF STUDENT HOSTELS AND CANTEENS IN A NIGERIAN UNIVERSITY CAMPUS: RISKS ON STUDENTS’ HEALTH (FUDMA JOURNAL OF SCIENCES, 2024)
Microbial air contaminants affect the quality of air we breathe and these microbial air contaminants can settle on body parts, clothes, food etc. which poses a serious threat to human health. Therefore, the level of bacterial contamination in various in-door air of the students’ hostels and canteens of Kaduna State University (KASU) and their antibiotics susceptibility patterns was studied. A total of 44 samples were collected from the rooms (18), toilets (18) of the students hostels and canteen (8) of KASU; using the settle plate method. Gram staining and standard biochemical methods were used to identify the bacterial isolates and antibiotic susceptibility testing was determined by disc diffusion method. The bacteria load was between 1.2 x 103 to 6.7 x 103 cfu/ml3. A total of 30 bacteria isolates were identified, Staphylococcus aureus had the highest (9, 30%) occurrence, followed by Streptococcus spp (6, 20%), Bacillus subtilis and Clostridium spp had similar (4, 13.2%) occurrence, The antibiotic susceptibility testing carried out revealed that the Gram negative and Gram positive bacteria isolates were more susceptible to vancomycin (75%, 43.5%), tetracycline (75%, 47.8%) and gentamicin (50%, 43.5%) while high resistance was observed with chloramphenicol (100%, 73.9%), ceftriaxone (100%, 100%), cefoxitin (100%, 73.9%), amoxicillin/clavulanic acid (100%, 87%), and trimethoprim/sulphamethoxazole (100%, 78%).  All the indoor samples were contaminated with pathogenic bacteria and there was high level of multidrug resistance.  This is very dangerous to the students’ health because it can be a source of transmission infections and antibiotic resistant bacterial strains.
Keywords: Indoor air; Assessment; M\icroorganisms; Quality